Crustal structure from the Hecataeus Rise to the Levantine Basin, eastern Mediterranean, from seismic refraction and gravity modelling. Issue 3 (3rd November 2015) - Welford, J. Kim; Hall, J.; Rahimi, A.; Reiche, S.; Hübscher, C.; Louden, K.
Abstract : In 2010, a wide-angle seismic reflection/refraction profile was acquired along the Hecataeus Rise, an area of shallow seabed immediately south of Cyprus in the eastern Mediterranean. The profile crossed from the Hecataeus Rise, through the Cyprus Arc to the Levantine Basin beyond. Due to the short length of the profile and the corresponding lack of deep ray coverage, velocity modelling was complemented by gravity modelling to gain constraints on deep crustal structure. The resultant model reveals velocities for the Hecataeus Rise that show no evidence of shallow ophiolites like those seen on mainland Cyprus, and the velocities are not diagnostic of a unique crustal affinity. Low-velocity sediments make up at least 7 km of the upper structure of Hecataeus Rise and these sediments overlie a two-layered crust. From the gravity modelling, the combined sediments and crust of Hecataeus Rise appear to be thinner than the Eratosthenes Seamount block to the southwest. A high-velocity lower crustal block is modelled under the seaward edge of Hecataeus Rise and, based on the gravity modelling, is inferred to extend landwards beneath the Rise. Similar high-velocity blocks were identified on the southwestern edge of Hecataeus Rise along nearby refraction lines and were interpreted as remnant Tethyan oceanic crust, foundered in the Cyprus Arc, along which subduction has ceased in this area. Given the thin two-layered crust beneath a thick accumulation of sediments modelled for Hecataeus Rise, we interpret that Hecataeus Rise represents a collage of oceanic fragments, accreted together within the failed subduction zone. Outboard of the crust of Hecataeus Rise, a 5-km deep low-velocity basin, possibly an accretionary wedge, is imaged that appears to correspond with the Cyprus Arc deformation zone imaged on both coincident and along-strike seismic reflection lines. A similar and wider feature is observed on seismic refraction lines to the west and combined, these may be revealing an eastward tapering zone of crustal deformation. To the south of the profile, the Levantine Basin appears undisturbed by the collision to the north and exhibits a uniform and homogeneous velocity structure.